RUâ€™YAT AL-HILÄ€L DENGAN TEKNOLOGI : Telaah Pelaksanaan Ruâ€™yat al-HilÄl di Baitul Hilal Teluk Kemang Malaysia - Pratama, Dito Alif (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2016)
Baitul Hilal Teluk Kemang which is located at coordinate latitude 2 Â° 26 '44' in the North and longitude 101Â° 51'21' in the East, is one of the good record crescent sighting observation center in Malaysia. The result of the study is as follows, firstly, the method of crescent observation at Baitul Hilal seems quite effective since it is located in a strategic and suitable place for crescent observation activity. Baitul Hilal is also supported by some sophisticated technology such as telescope and DSLR camera operated by some crescent observers who are officially certified by the Malaysian government. Secondly, Baitul Hilal has contributed to crescent observation development in Malaysia. Baitul Hilal also provides with the astronomical data based on monthly crescent activity as an additional data for crescent researcher to analyze the imká¾±n al-rukyah criterion.